Technological disaster’s criteria and models - Shaluf, Ibrahim M.; Ahmadun, Fakharul‐razi; Mustapha, Sa’ari (Emerald, 2003)
Disasters are classified as natural and man‐made disasters. Man‐made disaster, which occurs at the major hazard installation, is a technological disaster. For an incident to be classified as technological disaster criteria are required to be met. Several criteria have been proposed by researchers and agencies defining the disasters in terms of casualties, economic loss and environmental impact. Few models have been drawn describing the sequence of development of the technological disaster. This paper reviews in detail the proposed criteria, which define the disaster. The paper also summarizes the models which describe the disaster stages. Finally the paper summarizes a proposed model of the technological disaster precondition phase for major accidents.